SOFTWARE ANALYSIS OF AN AUTOMATED HYDROPONICS SYSTEM - Boboyorov Azizjan Eshmuminovich; Abdurashidov Firdaus Namoz o’g’li; Aliyev Olmos Vali o’g’li (Researchparks Publishing, 2023)
This article automated of hydroponics software supply done increase methods present is enough Today's in the day in the world to food has been Demand increased is going Hence hydroponics _ system software supply work out of farming new stable method and market economy we will develop .